2013
DOI: 10.1515/iral-2013-0006
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for linking information by German and Japanese native Speakers and by German learners of Japanese

Abstract: The study examines which strategies native speakers of German, native speakers of Japanese and advanced German learners of Japanese adopt when linking information in narrative texts (film retellings). The main results are as follows: (a) The L1 German speakers organize temporal shift-relations in order to link information, whereas the protagonist in topic function is often maintained across utterances. In contrast, the Japanese speakers prefer to compare series of events involving each of the main characters b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Of similarly close relevance to this study, Natale (2013) and Tomita (2013) identified symptoms of converged concepts in late bilinguals' narratives. Natale (2013) examined principles of subordination in the film retellings of French learners of Italian.…”
Section: Competition and Conceptual Convergence In Bilingualssupporting
confidence: 55%
See 2 more Smart Citations
“…Of similarly close relevance to this study, Natale (2013) and Tomita (2013) identified symptoms of converged concepts in late bilinguals' narratives. Natale (2013) examined principles of subordination in the film retellings of French learners of Italian.…”
Section: Competition and Conceptual Convergence In Bilingualssupporting
confidence: 55%
“…With focus on language production studies, evidence was documented both in favour of conceptual restructuring in the direction of the L2 (e.g., Cadierno, 2004; Hohenstein, Eisenberg & Naigles, 2006; Wolff & Ventura, 2009, for motion events), as well as against it (e.g., Cadierno & Ruiz, 2006, for voluntary and caused motion; Carroll & Lambert, 2003; Schmiedtová, von Stutterheim & Carroll, 2011, for event construal). Convergence in production patterns, i.e., linguistic performance not conforming to either the L1 or the L2 but found to be a hybrid of the source and the target patterns, was reported for language production of late bilinguals in the expression of caused motion (Hendriks, Hickmann & Demagny, 2008), in temporal subordination (Natale, 2013), additive and contrastive event linkage (Tomita, 2013), and also event linearization (Vanek, 2013).…”
Section: Competition and Conceptual Convergence In Bilingualsmentioning
confidence: 88%
See 1 more Smart Citation
“…von Stutterheim, 2003;Lambert et al, 2008, for spatial and temporal information; Bohnacker & Rosén, 2008, for the impact of information structure on word order; Ahrenholz, 2005;Leclercq & Lenart, 2013, for referring expressions). The picture emerging r om studies addressing the L2 acquisition of additive and contrastive linking of information units in discourse Benazzo et al, 2012;Tomita, 2013) is rather mixed. We will consider the fi ndings in more detail here, since the three studies are based 9.…”
mentioning
confidence: 99%
“…In the production domain, several lines of inquiry have been pursued to test how grammatical aspect systems in different languages modulate processes involved in retrieving event information from the knowledge base. The language combinations examined to date include Czech and Russian (Schmiedtová and Sahonenko 2008); Dutch, English and German (von Stutterheim et al 2009); Czech, English and Hungarian (Vanek and Hendriks 2015); Japanese and German (Tomita 2013), Swedish and Spanish (Bylund 2011). Analyses of video retellings showed that speakers of languages with the concept of ongoingness fully grammaticalised in T Vanek, N. & Mertins, B.…”
Section: Grammatical Aspect and Narrative Processingmentioning
confidence: 99%